2002
DOI: 10.1099/0022-1317-51-12-1097
|View full text |Cite
|
Sign up to set email alerts
|

Development of a PCR assay specific for Peptostreptococcus anaerobius

Abstract: Peptostreptococcus anaerobius is a gram-positive anaerobic coccus that is widely distributed in the normal human flora. The organism has also been implicated as a causative agent of several systemic infections, including endocarditis and infections of the genitourinary and gastrointestinal tracts. Its role in oral disease is less well defined, although it has been implicated in periodontal disease, gingivitis and root canal infections. Identification of P. anaerobius in clinical samples is currently reliant up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Downes and Wade (9) suggested that P. stomatis originates from the oral cavity, whereas P. anaerobius sensu stricto is involved in infections below the waistline. Their suggestion was consistent with a previous report of Riggio and Lennon (22), who failed to detect P. anaerobius in oral specimens by species-specific PCR. In line with these studies was our finding that most P. anaerobius isolates were from miscellaneous infectious specimens of the lower extremities and genitourinary tract.…”
supporting
confidence: 81%
“…Downes and Wade (9) suggested that P. stomatis originates from the oral cavity, whereas P. anaerobius sensu stricto is involved in infections below the waistline. Their suggestion was consistent with a previous report of Riggio and Lennon (22), who failed to detect P. anaerobius in oral specimens by species-specific PCR. In line with these studies was our finding that most P. anaerobius isolates were from miscellaneous infectious specimens of the lower extremities and genitourinary tract.…”
supporting
confidence: 81%
“…blotting with probes is labour-intensive. More recently, Riggio et al (2001) and Riggio & Lennon (2002) have developed PCR assays that specifically detect P. anaerobius and M. micros in clinical samples. In the present study, based on a 16S rDNA sequence analysis, we developed a multiplex PCR protocol which allows the rapid identification of 14 GPAC species, including eight clinically relevant species.…”
Section: Discussionmentioning
confidence: 99%
“…2). Interestingly, the specific forward primer described by Riggio & Lennon (2002) was designed to anneal to this region, making it specific for P. anaerobius, but not Peptostreptococcus CK035. This further supports the hypothesis that P. anaerobius is not found in the human mouth.…”
Section: Strains W2175 W2205 and W2278mentioning
confidence: 99%
“…However, a specific PCR assay for the species (Riggio & Lennon, 2002) failed to detect P. anaerobius in any of 60 subgingival plaque samples collected from subjects with periodontitis or 43 pus samples from dentoalveolar abscesses.…”
mentioning
confidence: 98%